A single institution experience with proximal junctional kyphosis in the context of existing classification schemes – Systematic review. (June 2021) - Elarjani, Turki; Basil, Gregory W.; Kader, Michael Z.; Pinilla Escobar, Victoria; Urakov, Timur; Wang, Michael Y.; Levi, Allan D.
Highlights: Proximal junctional kyphosis has two widely known classification systems. Current classifications measure the mechanism of failure and severity with treatment indication. Future classification systems should incorporate etiology, mechanism of failure, and severity. Abstract: Background: Proximal junctional kyphosis is a kyphotic deformity following spine instrumentation, predominantly seen in scoliosis patients. There have been previous attempts to develop classification schema of PJK. We analyzed the factors contributing to PJK based upon our own clinical experience with the goal of developing a clinical guidance tool which took into account both etiology and mechanism of failure. Methods : We performed a retrospective analysis of all re-operation thoracolumbar surgeries at a single institution over a 14-year period. Patients with PJK were identified and categorized based upon the etiology, mechanism of failure, and an indication of revision. Next, we conducted a systematic review on articles emphasizing a classification system for PJK. Results : Fourteen PJK patients were identified out of 121 patients who required revision spine surgery. The average age was 64.9 ± 10.2 years, with 10 males (71%) and 4 females (29%). Three primary etiologies were identified: 6/14 (47%) overcorrection, 6/14 (47%) osteopenia, and 2/14 (14%) ligamentous disruption. The mechanism of failure was likewise divided into three categories: 9/14 (64%) compression fracture, 1/14 (7%) hardware failure, and 4/14 (29%) disc degeneration. The relationship between osteopenia and the development of a compression fracture leading to PJK was statistically significant (p = 0.031). Conclusion : There are multiple current classification systems for PJK. Our study findings were in line with previously published literature and suggest the need for a future classification system combining both etiology, mechanism of failure, and severity of disease.